Analissi Parameter Directional Drilling dengan Menggunakan Metode Radius of Curvature untuk Penentuan Lintasan Sumur “FJ-07 Lapangan SS” - Muhammad Restu Alparesh; Muhammad Fajrin Al Fattah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study evaluates the application of the Radius of Curvature method for determining the directional well trajectory of FJ-07 in the SS Field, located beneath a river area, where accurate well trajectory planning is essential. A descriptive quantitative approach was employed using Measurement While Drilling (MWD) survey data, including Measured Depth (MD), inclination, and azimuth. The True Vertical Depth (TVD), North, and East coordinates were calculated numerically using Microsoft Excel and compared with the company's reference data generated using the Minimum of Curvature method. The results indicate that the Radius of Curvature method produced only minor deviations from the reference data, ranging from 0.3–0.6 ft for TVD, 3–6 ft for North, and 0.8–1.2 ft for East. These deviations are within acceptable engineering tolerances, indicating that the Radius of Curvature method is a reliable alternative for directional well trajectory planning and evaluation.